The Evaluation of Character Education Program Implementation in Al-Azhar Islamic Elementary School Kelapa Ivory North Jakarta - Jumadi JUMADI; Sutjipto SUTJIPTO; Ivan HANAFI (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to explain, uncover facts, obtain empirical findings and recommendations in the form of guidelines for the Implementation of the Character Education Program at Al-Azhar Islamic Elementary School Kelapa Gading, North Jakarta which includes context, input, process, and results. The research uses a qualitative approach through the CIPP evaluation model (Context, Input, Process, and Product). Collecting data using interview, observation, and document review. The research informants were the Principal, Deputy Principal, Educators/Teachers, Education Personnel, Students, and Head of School Committees. The validity of the data quality test was carried out through triangulation of data, sources, methods and time. The results of the Context Evaluation study which included the vision and mission, programs, program objectives showed very good results, for the Input Evaluation which included program strategy, program design, character education program plans, and resource readiness showed very good results, for Process Evaluation which included implementation the character education program has been running very well, and for the Outcome Evaluation including the results of the program achievements, the results are very good. From the results of the overall evaluation, the program can be continued because the implementation of the program shows that all aspects have been running according to the goals and expectations and provide results and benefits, even the program needs to be spread in other places because the program has succeeded very well.